Simulation training in endoscopic skull base surgery: A scoping review. Issue 1 (31st March 2022) - James, Joel; Irace, Alexandria L.; Gudis, David A.; Overdevest, Jonathan B.
Abstract: Objective: Proficiency in endoscopic endonasal skull base surgery requires both substantial baseline training and progressive lifelong learning. Endoscopic simulation models continue to evolve in an effort to optimize trainee education and preoperative preparation and improve surgical outcomes. The current scoping review systematically reviews all available literature and synthesizes the current paradigms of simulation models for endoscopic skull base surgery training and skill enhancement. Methods: In accordance with Preferred Reporting Items for Systemic Review and Meta‐Analyses guidelines, we systematically searched PubMed, Embase, CINAHL, and Cochrane databases. Studies were categorized according to the type of simulation models investigated. Results: We identified 238 unique references, with 55 studies ultimately meeting inclusion criteria. Of these, 19 studies described cadaveric dissection models, 17 discussed three‐dimensional (3D) printed models, 14 examined virtual surgical planning and augmented reality‐based models, and five 5 articles described task trainers. Conclusions: There are a wide variety of simulation models for endoscopic skull base surgery, including high‐fidelity cadaveric, virtual reality, and 3D‐printed models. These models are an asset for trainee development and preoperative surgical preparation.